Pelatihan Ecoprint Sebagai Media Edukasi Lingkungan Bagi Masyarakat RW 03 Kelurahan Samaan - Sa'ida Tushofiyah; Hana Widya Ningrum; Naufal Maulana Rafiq; Qonitatus Sholihah; Achmad X-One Putra Masruro; Amelia Wira Andini Firdaus; Febrian Dwi Prayoga; Khairunnisa Qoulan Sadida; Muhammad Ata Safaraz Hidayat; Muhammad Fadin Ramadhan; Nabila Diva Wida Siswanto; Muhammad Difa’ul Haqqi; Serli Agustin; Shafira Hanifa; Rizqi Sayla Ramadlani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This community service activity was conducted to introduce ecoprint as an environmentally friendly textile dyeing technique and to increase environmental awareness among residents of RW 03 Kelurahan Samaan. The activity used a Community-Based Research approach with participatory hands-on training. The program was carried out in one day and included preparation, training implementation, and evaluation. Participants received material on the environmental impacts of synthetic dyes and learned basic principles of natural dyeing using local plant materials. They practiced arranging leaves and flowers on fabric and transferring natural pigments through a simple ecoprint process. The results showed that participants produced fabrics with diverse natural motifs and improved their understanding of eco-friendly dyeing. Evaluation indicated increased knowledge, practical skills, and environmental awareness, and highlighted the potential of ecoprint as a creative product based on local resources. These findings suggested that short-term training effectively supported community learning and sustainable textile practices in this setting.